ANALISIS BREAK EVENT POINT DI SMK NEGERI I KARANGANYAR TAHUN PELAJARAN 2012/2013 - Sri - Haryono (Universitas Slamet Riyadi, 2014)
The objective of this research is to calculate break event point of the real education cost in Vocational High School 1 of Karanganyar in 2012/2013. So as be able to know the cost of education will be certified by each student in Vocational High School 1 of Karanganyar. The sample or research object is Vocational High School 1 of Karanganyar. This research is a study case research by employing descriptive quantitative analysis break event point calculation method and operational education cost per month for each student. The calculation is done based on cash basis.The break event calculation for the factual condition of Vocational High School 1 of Karanganyar in 2012/2013 obtain the result: (1) break event point in rupiah currency in the amount of Rp 522.489,12; (2) break event point in a unit total 1, 608 students. The calculation of education cost by a traditional approach in Vocational High School 1 of Karanganyar in 2012/2013 gain the result: (1) The total of education cost per year is Rp 9.929.714.726,80; (2) The education cost per year for each student is Rp 6.852.804,19; and (3) The education cost per month for each student is Rp 571.067,10. The factual condition from the education cost in Vocational High School 1 of Karanganyar shows pattern with a traditional approach. The education cost is adopted to each student proved to be very low compared to the actual cost charged to the students. The government fund support still dominate education funding in Vocational High School 1 of Karanganyar. Keywords: education cost, break event point, unit cost